The Footprint as an Accelerator for Individualisation and Relation: Patrick Chamoiseau’s L’empreinte à Crusoé - Kopf, Martina (Porównania, 2019)
Starting with Defoe’s famous footprint scene, this contribution focuses on the Martiniquan author Patrick Chamoiseau’s rewriting of Robinson Crusoe L’empreinte à Crusoé (2012). In this polyphonic novel, the footprint becomes an accelerator for individualisation and relation. After discovering the footprint, Chamoiseau’s Robinson, a black amnesic African, is obsessed by the possible presence of another. He puts into question his identity and enters into a new relation with the whole island, its flora and fauna. The novel might be seen as a poetical transformation of Chamoiseau’s theoretical and poetological ideas on creolization which are developed in the manifesto of the creoleness movement In Praise of Creoleness. The footprint thus becomes a symbol for the creolization processes.